Vascular adaptations and hemodynamic consequences of Thoracic Outlet Compression in overhead athletes – a comprehensive review - Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Kaczmarek , Aleksandra; Kaczmarek , Wojciech; Krakowiak, Magdalena; Gołacki, Rafał; Jabłonowska, Magdalena; Bagiński, Konrad; Jurczuk, Aleksandra (Quality in Sport, 2025)
Introduction: Thoracic outlet syndrome (TOS) encompasses a range of disorders caused by compression of the neurovascular bundle at the thoracic outlet. Overhead athletes are at elevated risk due to repetitive overhead motion, muscle hypertrophy, and sport-specific biomechanics. Vascular compression, particularly of the subclavian vein and artery, induces distinct hemodynamic changes that may impair athletic performance and predispose to complications such as effort thrombosis, stenosis, and distal embolization [1–3]. This review paper aims to to synthesize current evidence regarding vascular adaptations, hemodynamic consequences, diagnostic strategies, and management approaches for thoracic outlet compression in overhead athletes. Materials and methods: Literature from 2015–2025 was systematically searched through PubMed, Scopus, and Google Scholar using the terms: “thoracic outlet syndrome,” “overhead athletes,” “Paget-Schroetter syndrome,” “effort thrombosis,” “vascular compression,” and “rehabilitation.” Priority was given to systematic reviews, clinical trials, and high-quality case studies [4–6]. Summary: Vascular TOS in athletes manifests as venous thrombosis or stenosis due to repetitive microtrauma and hypertrophy of the scalene and pectoralis minor muscles [7–9]. Dynamic ultrasonography, MR angiography, and advanced 4D flow imaging enhance detection of flow disturbances during provocative maneuvers. Management includes conservative rehabilitation and surgical decompression, with individualized return-to-play protocols optimizing vascular recovery and functional outcomes [10–14]. Conclusions: Thoracic outlet compression represents an underrecognized but clinically significant cause of vascular dysfunction in overhead athletes. Early recognition, tailored management, and preventive training interventions are critical for preserving vascular health and athletic performance [15,16].